TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) DAN IMPLEMENTASINYA - Suparnyo Suparnyo (Faculty of Law, Universitas Diponegoro, 2010)
Economic activities are done by economic agents on the purpose of getting profit. However, in getting the profit, a corporation may not harm or ignore other parties'interest, or in other words, it must be responsible either juridically or socially. The problems to discuss in this study are as follows : (1) To what extent is the Corporate Social Responsibility (CSR) implemented? (2) What factors are to motivate a corporation to implement its Corporate Soocial Responsibility (CSR)? (3) What moral value or what legal principles are to be accommodated by future legislations (ius constituendum) so that a balance between corporative interest and public interest can be archived? The above problems are analyzed under the framework of Justice Theory, Social Contract Theory, Structural and Functional Theory, Stakeholders Theory, and Utilitarianism Theory. Primary and Secondary data are comprehensively processed into narrations and table formats by using empirical jurisdiction approach, and further study about the implementation of Corporate Social Responsibility; the factors motivating a corporation to implement its social responsibility; and to find a model of moral values and legal principles which can be accomodated for future legislation (ius costituendum. In reality, the implementations of CSR are still on the social awareness level, in the form of charity donation and some of CSR implementations are still directed to community affairs. The implementations of Corporate Social Responsibility are influenced by both internal and external drivers of the corporations. Sense of concern on stakeholders is an internal driver of a coporation to implement CSR.